Pedagogia em ambientes não escolares: a importância da arteterapia nas ações do Centro de Atenção Psicossocial Infanto-juvenil - DIAS, Raqueline da Silva (2023)
This study originates from the reflections developed in the Curricular Activity of Supervised Internship in Non-School Environments of the Degree Course in Pedagogy of the Faculty of Education of the University Campus of Altamira of the Federal University of Pará, in the period from March 14 to 29, 2022 at the Child and Adolescent Psychosocial Care Center (CAPSi) of the municipality of Altamira-PA. It also enters into the historical process that was the Psychiatric Reform in Brazil until the implementation of the Psychosocial Care Centers (CAPS), With this, it was questioned: What is the importance of art therapy in psychopedagogical care in the Child and Youth Psychosocial Care Center in the Municipality of Altamira-PA?, as well as aimed to reflect on the use of art therapy in the CAPSi of the Municipality of Altamira / PA, in the year 2022. As specific objectives: a) To identify the art therapy actions that are carried out in CAPSi; b) Discuss the art therapy actions of CAPSi; c) To analyze the art therapy actions developed in the pedagogical interventional participation in CAPSi. The study has a qualitative approach and field research, with emphasis on participant observation in the actions of workshops and groups of care for children users of CAPSi, as well as in the aid of the activities developed by the children, in addition to putting into practice the knowledge acquired in the training process, through psychopedagogical intervention, anchored to art therapy. Such experience is fundamental and contributory to the full development as a future professional. It was concluded that many still have a retrograde view that connects the work of the pedagogue only to school institutions, however, the professional is qualified to work in the most diverse areas, including those related to mental health.